Psychology: what it has to teach you about yourself and the world you live in - Martin, Everett Dean (The people's institute "Lectures-in-print" series, 1924)
Pt. 1. What psychology really is - its uses and abuses.- Pt. 2. Psychology and physiology, a study of reactions.- Pt. 3. Psychology and philosophy - The place of William James.- Pt. 4. Psycho-analysis - What Freud and his followers have done for psychology.- Pt. 5. What psychologists think about consciousness.- Pt. 6. the fatality of habits.- Pt. 7. Human nature and the problems of instinct.- Pt. 8. Man and his emotions.- Pt. 9. A lecture on how we think.- Pt. 10. The value of the fictions we invent about ourselves.- Pt. 11. The unconscious and its influence upon human behavior.- Pt. 12. The significance of the intelligence tests.- Pt. 13. Is there a group mind? What governs the behavior of people in society?- Pt. 14. The psychology of propaganda and public opinion.- Pt. 15. The psychology of religion.- Pt. 16. The psychology of politics.- Pt. 17. Are there psychological differences of race?- Pt. 18. Ethics in the light of psychology.- Pt. 19. Behaviorism - The latest and most debated development.- Pt. 20. How much progress can human nature stand?